1999
DOI: 10.1128/aac.43.5.1234
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effect of 2′,6′-Dihydroxy-4′-Methoxychalcone Isolated fromPiper aduncumonLeishmania amazonensis

Abstract: 2′,6′-Dihydroxy-4′-methoxychalcone (DMC) was purified from the dichloromethane extract of Piper aduncum inflorescences. DMC showed significant activity in vitro against promastigotes and intracellular amastigotes of Leishmania amazonensis, with 50% effective doses of 0.5 and 24 μg/ml, respectively. Its inhibitory effect on amastigotes is apparently a direct effect on the parasites and is not due to activation of the nitrogen oxidative metabolism of macrophages, since the production of nitric oxide by both unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(89 citation statements)
references
References 36 publications
6
81
0
2
Order By: Relevance
“…The ultrastructural changes shown in the promastigotes of L. (L.) amazonensis in this report are similar to those observed by other authors (Vannier-Santos et al 1995;Torres-Santos et al 1999;Delorenzi et al 2001;Rodrigues et al 2002;Rosa et al 2003;Brenzan et al 2007;Rodrigues et al 2008). Untreated L. amazonensis promastigotes showed typical morphology.…”
Section: Discussionsupporting
confidence: 93%
“…The ultrastructural changes shown in the promastigotes of L. (L.) amazonensis in this report are similar to those observed by other authors (Vannier-Santos et al 1995;Torres-Santos et al 1999;Delorenzi et al 2001;Rodrigues et al 2002;Rosa et al 2003;Brenzan et al 2007;Rodrigues et al 2008). Untreated L. amazonensis promastigotes showed typical morphology.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Braga et al (2004) showed that the presence of ergosterol and analogs is essential for the maintenance of normal structural organization, especially of the inner mitochondrial membrane, in these protozoa. Several studies have also shown ultrastructural alterations in Leishmania amazonensis treated with synthetic or natural compounds (Torres-Santos et al 1999;Rodrigues et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…19 Pinostrobin chalcone has been isolated from Piper aduncum and exhibits significant activity against Leishmania amazonensis. 20 It has also been reported as a constituent of Egyptian 21 and Brazilian 22 propolis. Scopoletin and scoparone are simple coumarins that have been isolated from various botanical species.…”
Section: Resultsmentioning
confidence: 99%